An Enhanced Positional Error Compensation Method for Rock Drilling Robots Based on LightGBM and RBFN - Zhou, Xuanyi; Bai, Wenyu; He, Jilin; Dai, Ju; Liu, Peng; Zhao, Yuming; Bao, Guanjun (Frontiers in Neurorobotics, 2022)
Rock drilling robot is able to greatly reduce labor intensity and improve efficiency and quality in tunnel construction. However, due to the characteristics of the heavy load, large span, and multi-joint of the robot manipulator, the errors are diverse and non-linear, which poses challenges to the intelligent and high-precision control of the robot manipulator. In order to enhance the control accuracy, a hybrid positional error compensation method based on Radial Basis Function Network (RBFN) and Light Gradient Boosting Decision Tree (LightGBM) is proposed for the rock drilling robot. Firstly, the kinematics model of the robotic manipulator is established by applying MDH. Then a parallel difference algorithm is designed to modify the kinematics parameters to compensate for the geometric error. Afterward, non-geometric errors are analyzed and compensated by applying RBFN and lightGBM including features and kinematics model. Finally, the experiments of the error compensation by combing the geometric and non-geometric errors verify the performance of the proposed method.